Determination of Urinary Oxalate with Arylamine Glass-Bound Sorghum Oxalate Oxidase and Horseradish Peroxidase - Thakur, M.; Bhargava, A.K.; Pundir, C.S. (International Journal of Applied Sciences and Biotechnology, 2016)
We describe an enzymic colourimetric method for determination of oxalate level in urine using arylamine glass-bound sorghum leaf oxalate oxidase and horseradish peroxidase. The method is based on quantification of H2O2 generated from oxidation of urinary oxalate by immobilized oxalate oxidase, by a colour reaction consisting of 4-aminophnazone, phenol and immobilized peroxidase as chromogen. Minimum detection limit of the method was 0.05 mmol/l. Analytical recovery of added oxalate in urine was 96.8± 3.0% (mean ±S.D.). Within and between day coefficient of variation (CV) for urinary oxalate in urine were < 3.5% and <6.46 % respectively. The urinary oxalate values in apparently healthy and urinary stone formers as measured by the present method were correlated with those by modified Sigma Kit method (r= 0.929). The method has the advantages that it provides ca 200 times reuse of oxalate oxidase and peroxidase and free from interferences by Cl- and NO3- normally found in urine. Int J Appl Sci Biotechnol, Vol 4(3): 346-351